Body Mass Index and its relation with Hypertension, Diabetes Mellitus and Ischemic Heart Disease in a General Health Clinic in Nepal - Aacharya, R.P.; Prasad, P.N.; Gupta, M.P. (Journal of Institute of Medicine Nepal, 2007)
Background: Obesity is increasing rapidly in both developed and developing countries and the new generations are at increased risk. Similarly, the prevalence of non-communicable diseases are also increasing. In this context, attempt has been made to correlate the situation. Objective: To find out the Body Mass Index (BMI) in patient suffering from three common non-communicable diseases - hypertension, diabetes mellitus and ischemic heart disease (IHD). Materials and Methods: A retrospective study was carried out in the clients attending General Health Check up Clinic at Tribhuvan University Teaching Hospital, Katmandu during a period of six months. Those suffering from Hypertension, Diabetes Mellitus and Ischaemic Heart Disease were included and BMI was analysed. Results: In this study, a total of 464 records were analyzed. Analysis of BMI revealed 5.8% to be underweight (<18.5), 52.2% to be normal (18.5-25.0), 37.9% to be overweight (25.1-30.0) and 4.1% to be obese (>30.0). Out of 19 obese cases, 73.7% had hypertension, 10.5% had diabetes mellitus and 5.3% had IHD. Similarly, out of 176 overweight cases 46.0% had hypertension, 6.8% had diabetes mellitus and 3.4% had IHD. The cases with normal weight or underweight had significantly lower incidence of these diseases. Out of 242 normal cases, 21.1% had hypertension, 5.4% had diabetes mellitus and 2.9% had IHD. Out of 27 underweight cases, 3.7% had hypertension, 3.7% had diabetes mellitus and none had IHD. Conclusion: This study showed that overweight and obesity is not uncommon in Nepali population; and is related with the higher incidence of hypertension, diabetes mellitus and IHD. Journal of Institute of Medicine Vol.28(1) 2006